Corporate Social Responsibility Reporting in the Enlarged European Union: An Eleven Country Study - Owens, Graham John (2003)
The aim of this research project is to study corporate social responsibility (CSR) reporting from organisations whose base country is in one of eleven countries in the proposed enlarged European Union (EU). Five of the countries awaiting formal entry to the EU, namely the Czech Republic, Hungary, Lithuania, Poland and Slovenia, whilst the other six have been members for a number of years, the United Kingdom, France, Germany, Ireland, Spain and Portugal. The paper investigates the reporting of twenty characteristics identified by the author as being important indicators of CSR activity in three categories: corporate governance, social policy and environmental policy. It recognises that although organisations may be reporting such activity it does not necessarily conclude that the actions are thoroughly integrated into the operational mechanisms of the organisations and are purely the organisations own view of how they approach the issues associated with being a ‘good corporate citizen’. The research found that the level of CSR reporting throughout the eleven countries in the study was generally of a high standard and easy to access. It should be enough to satisfy the stakeholders’ thirst for information. However the conclusions show that whilst the countries of Central and Eastern Europe have started to consider CSR reporting and many are reporting some form of activity, those who are multinational organisations and appear to have taken up the challenge better than organisations who are nationally based. There is also evidence that in the early stages of CSR reporting that sectors who have been targets of stakeholder angst such as pharmaceuticals and oil and gas corporations have taken to reporting in far more comprehensive way than others.